Relationship between the Total Quality Recovery Scale and race performance in competitive college swimmers over two seasons - Kato, T.; Kasugai, R.; Sakai, K. (Sports, 2025)
Background: Tapering, a period of reduced training load following intense training, contributes to performance enhancement. However, research on recovery status during tapering is limited. This study investigates the impact of recovery status on race performance.